Towards a dialogical method. Dialogue as a tool for knowledge and design - Zingale, Salvatore (E|C, 2020)
Dialogue is not just a comparison between different opinions and visions, but also an opportunity for “active observation” on field and for the study of behavior and social habits. In addition to this, dialogue is a tool for research for new knowledge and co-design procedure. However, this is a “neglected argument” from the semiotic studies, albeit with great potential. This paper aims to identify some prerequisites for a dialogic method, starting from the tripartition of the dialogues by Bonfantini and Ponzio and from the vision of dialogue in an epistemological way by David Bohm.